External validation of the Hospital Frailty Risk Score in France. (26th June 2021) - Gilbert, Thomas; Cordier, Quentin; Polazzi, Stéphanie; Bonnefoy, Marc; Keeble, Eilìs; Street, Andrew; Conroy, Simon; Duclos, Antoine
Abstract: Background: The Hospital Frailty Risk Score (HFRS) has made it possible internationally to identify subgroups of patients with characteristics of frailty from routinely collected hospital data. Objective: To externally validate the HFRS in France. Design: A retrospective analysis of the French medical information database. Setting: 743 hospitals in Metropolitan France. Subjects: All patients aged 75 years or older hospitalised as an emergency in 2017 ( n  = 1, 042, 234). Methods: The HFRS was calculated for each patient based on the index stay and hospitalisations over the preceding 2 years. Main outcome measures were 30-day in-patient mortality, length of stay (LOS) >10 days and 30-day readmissions. Mixed logistic regression models were used to investigate the association between outcomes and HFRS score. Results: Patients with high HFRS risk were associated with increased risk of mortality and prolonged LOS (adjusted odds ratio [aOR] = 1.38 [1.35–1.42] and 3.27 [3.22–3.32], c-statistics = 0.676 and 0.684, respectively), while it appeared less predictive of readmissions (aOR = 1.00 [0.98–1.02], c-statistic = 0.600). Model calibration was excellent. Restricting the score to data prior to index admission reduced discrimination of HFRS substantially. Conclusions: HFRS can be used in France to determine risks of 30-day in-patient mortality and prolonged LOS, but not 30-day readmissions. Trial registration: Reference ID on clinicaltrials.gov: ID: NCT03905629.